Glass cloth roll

The glass cloth roll is designed to address uneven heat treatment issues by optimizing the tensile strength ratio and color difference through specific manufacturing processes, resulting in improved resin impregnation and heat resistance uniformity for prepregs.

JP2025054507APending Publication Date: 2025-04-08UNITIKA GLASS FIBER CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023163573
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing batch method for heat cleaning glass cloth rolls often results in uneven heat treatment between the inner and outer layers, leading to differences in resin impregnation and heat resistance when used as prepregs for printed circuit boards.

Method used

A glass cloth roll is developed with a specific tensile strength ratio and color difference between layers, achieved by weaving a live machine cloth with a high ignition weight loss, followed by a water washing treatment to reduce ignition loss, and then a batch-type heat cleaning process with a winding thickness of 80 mm or less.

Benefits of technology

This approach reduces the difference in resin impregnation and heat resistance between the inner and outer layers of the glass cloth roll, improving the uniformity of the prepreg quality in the longitudinal direction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054507000001_ABST
    Figure 2025054507000001_ABST
Patent Text Reader

Abstract

To provide a glass cloth roll capable of reducing a difference between an inner layer and an outer layer of the glass cloth roll in resin impregnation property and heat resistance when forming a prepreg for a printed circuit board, while suppressing a decrease in a tensile strength in a warp direction.SOLUTION: In a glass cloth roll formed by winding a glass cloth composed of a glass yarn as warp and weft, a tensile strength represented by a ratio (T / M) of a tensile strength T (N / 25 mm) in the warp direction of the glass cloth to a mass M (g / m2) of the glass cloth is 3.8 or more and 6.0 or less, and a color difference ΔE between the outermost layer portion and the innermost layer portion of the glass cloth roll is 0.1 or more and 1.5 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass cloth roll. [Background technology]

[0002] Glass cloth is composed of a yarn in which a plurality of long glass fibers (filaments) are bundled together. Glass yarn and glass cloth for printed wiring boards are mainly manufactured through a glass yarn manufacturing process including a spinning process and a twisting process, and a glass cloth manufacturing process including a warp yarn preparation process, a weaving process, a heat cleaning process, and a surface treatment process. The operation details in each process are as follows.

[0003] (A) Glass yarn manufacturing process (A-1) Spinning process Glass raw materials are melted in a glass melting furnace and drawn out as a plurality of long glass fibers, which are then bundled with a bundling agent to form a wound glass strand called a cake. (A-2) Yarn twisting process Glass strands are pulled from the cake and twisted in a twisting machine to form glass yarn. (B) Glass cloth manufacturing process (B-1) Preparation process Glass yarn is used to prepare the warp yarn for the glass cloth through processes such as warping, sizing, and drawing. (B-2) Weaving process The prepared warp yarns and glass yarns as weft yarns are woven by an air jet loom or the like to produce a grey cloth. (B-3) Heat cleaning process (heat de-oiling process) Sizing agents and the like applied to the surfaces of the long glass fibers during the spinning process can impair the adhesion between the long glass fibers and the matrix resin during prepreg production. Therefore, a heat cleaning treatment (thermal deoiling treatment) is carried out to remove organic components such as sizing agents adhering to the glass cloth by heating. (B-4) Surface treatment process In the production of prepregs, in order to improve the adhesion between the matrix resin and the long glass fibers, the glass cloth that has been heat-cleaned is treated with a silane coupling agent.

[0004] Typically, heat cleaning is carried out using a batch method in which a roll of grey cloth wrapped around a metal core is placed in a heating furnace and heated to a temperature of around 400°C.

[0005] As a method of heat cleaning treatment, for example, a method of heat cleaning glass fabrics is known, which is characterized by heating a glass fabric sized with a warp sizing agent for glass fabrics, the warp sizing agent being mixed with a thermal decomposition promoting substance in an amount of 0.03 to 1% by weight based on the solid content of the sizing agent, under a reducing atmosphere to thermally decompose the warp sizing agent (see, for example, Patent Document 1). According to this heat cleaning method, it is said that the primary binder and the warp sizing agent can be easily removed from the sized glass fabric at a relatively low temperature even in a reducing atmosphere.

[0006] As a method of heat cleaning treatment, for example, a method of heat cleaning a glass fiber fabric is known, which is characterized by contacting a glass fiber fabric obtained by weaving glass fiber bundles coated with an organic substance with an aqueous acetic acid solution, and then heat treating the fabric at an atmospheric temperature of 350 to 700° C. (See, for example, Patent Document 2.) This heat cleaning method is said to be able to suppress carbonization of the organic substance due to heating, and to enable efficient heat cleaning treatment without causing poor appearance such as black spots on the glass fiber fabric. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 7-197380 [Patent Document 2] Patent Publication No. 2007-262629 Summary of the Invention [Problem to be solved by the invention]

[0008] For example, when the heat cleaning process is performed in a batch manner as in Patent Documents 1 and 2, the glass cloth is wound around an iron core in a roll shape, so that the inner layer part of the glass cloth roll subjected to the heat cleaning process is likely to be insufficient in air supply from the outside, and is heated in a state of insufficient oxygen. As a result, after the heat cleaning process, the inner layer part is likely to have a lower degree of removal of organic components attached to the glass cloth, such as a bundling agent, than the outer layer part of the glass cloth roll subjected to the heat cleaning process. That is, unevenness in the heat cleaning process is likely to occur between the inner layer part and the outer layer part. And, if unevenness in the heat cleaning process occurs between the inner layer part and the outer layer part, unevenness also occurs in the resin impregnation and heat resistance when the prepreg for printed wiring board is made, and it is likely to be difficult to obtain a prepreg having uniform quality in the longitudinal direction of the glass cloth.

[0009] On the other hand, in the above Patent Documents 1 and 2, if the temperature conditions of the heat cleaning treatment are increased or the time of the heat cleaning treatment is extended in order to prevent unevenness in the heat cleaning treatment between the inner layer portion and the outer layer portion, the tensile strength of the obtained glass cloth is reduced, and the glass cloth may break when it is made into a prepreg for a printed wiring board. Such a problem occurs when the mass (g / m2) of the glass cloth is increased. 2 ) is lower, it is more noticeable.

[0010] Therefore, the main object of the present invention is to solve the above problems and to provide a glass cloth roll which can suppress a decrease in tensile strength in the warp direction while reducing the difference in resin impregnation property and heat resistance between the inner layer and the outer layer of the glass cloth roll when it is made into a prepreg for printed circuit boards. [Means for solving the problem]

[0011] The present inventors have conducted intensive research to solve the above problems, and have found that a glass cloth roll having a glass cloth formed of glass yarns as warp and weft yarns and a mass M (g / m2 It has been found that the above problems can be solved by providing a glass cloth roll having a tensile strength expressed as a ratio (T / M) of the tensile strength T (N / 25mm) in the warp direction of the glass cloth to the tensile strength T (N / 25mm) in the warp direction of the glass cloth to the tensile strength T (N / 25mm) in the warp direction of the glass cloth, of 3.8 to 6.0, and a color difference ΔE between the outermost layer part and the innermost layer part of the glass cloth roll of 0.1 to 1.5. It has also been found that the glass cloth roll can be obtained by weaving a greige cloth so that the ignition loss of the warp is 2.5% by mass or more, washing the same with water before carrying out a heat cleaning treatment so that the ignition loss of the warp is 2.0% by mass or less, and then carrying out a heat cleaning treatment in a batch-type heat cleaning method with a winding thickness of 80 mm or less. The present invention is an invention that has been completed based on such findings and through further intensive studies.

[0012] That is, the present invention provides the following aspects. Item 1. A glass cloth roll in which a glass cloth composed of glass yarns as warp and weft is wound, the mass M (g / m 2 a tensile strength expressed as a ratio (T / M) of a tensile strength T (N / 25 mm) in the warp direction of the glass cloth to a tensile strength T (N / 25 mm) in the warp direction of the glass cloth to a tensile strength T (N / 25 mm) in the warp direction of the glass cloth is 3.8 to 6.0, and a color difference ΔE between an outermost layer portion and an innermost layer portion in the glass cloth roll is 0.1 to 1.5. Item 2. The glass cloth roll according to item 1, wherein the color difference ΔE is 0.2 or more and 0.7 or less. Item 3. A method for producing a glass cloth roll according to item 1 or 2, comprising: a greige cloth preparation step of preparing a greige cloth having a warp thread loss on ignition of 2.5% by mass or more; a water washing step of subjecting the prepared greige cloth to a water washing treatment so that the warp thread loss on ignition is 2.0% by mass or less; and a heat cleaning step of winding the water-washed glass cloth into a roll having a thickness of 80 mm or less and subjecting it to a heat cleaning treatment. Effect of the Invention

[0013] According to the glass cloth roll of the present invention, a glass cloth formed of glass yarns as warp and weft is wound on the glass cloth roll, and the mass M (g / m 2 The tensile strength expressed as the ratio (T / M) of the tensile strength T (N / 25 mm) in the warp direction of the glass cloth to the tensile strength T (N / 25 mm) in the warp direction of the glass cloth is 3.8 to 6.0, and the color difference ΔE between the outermost layer part and the innermost layer part in the glass cloth roll is 0.1 to 1.5. This makes it possible to reduce the difference in resin impregnation property and heat resistance between the inner layer and the outer layer of the glass cloth roll when they are made into a prepreg for printed circuit boards, while suppressing a decrease in the tensile strength in the warp direction. [Brief description of the drawings]

[0014] [Figure 1] This is a schematic diagram explaining the measurement of the winding thickness of a glass cloth roll 1 wound around an iron core 2 before heat cleaning treatment, and is a schematic diagram of the end face of the glass cloth roll (corresponding to the bottom part of the cylindrical shape) viewed from a planar direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The glass cloth roll of the present invention is a glass cloth roll wound with a glass cloth composed of glass yarns as warp and weft, and the mass M (g / m 2 The tensile strength, expressed as the ratio (T / M) of the tensile strength T (N / 25 mm) in the warp direction of the glass cloth to the tensile strength T (N / 25 mm) in the warp direction of the glass cloth, is 3.8 to 6.0, and the color difference ΔE between the outermost layer portion and the innermost layer portion in the glass cloth roll is 0.1 to 1.5. The configuration of the glass cloth roll of the present invention will be described in detail below.

[0016] [Glass material] In the present invention, the glass yarn constituting the glass cloth is preferably a glass yarn in which a plurality of long glass fibers are bundled and twisted together. The glass material constituting the long glass fibers is not particularly limited. For example, E glass, T glass, S glass, UT glass, D glass, NE glass, L glass, LU glass, C glass, or AR glass manufactured by Unitika Ltd. may be mentioned.

[0017] From the viewpoint of versatility, it is preferable to use long glass fibers having an E-glass composition, which contains, relative to the total amount of the long glass fibers, SiO2 in the range of 52-56 mass%, B2O3 in the range of 5-10 mass%, Al2O3 in the range of 12-16 mass%, CaO and MgO in the range of 20-25 mass% in total, and Li2O, K2O and Na2O in the range of 0-1 mass% in total.

[0018] From the viewpoint of further increasing the strength of the prepreg and the printed wiring board, the long glass fibers are preferably made of a glass material containing, with respect to the total amount of the long glass fibers, 60 to 66 mass % of SiO2, 20 to 26 mass % of Al2O3, and 10 to 15 mass % of MgO.

[0019] From the viewpoint of lowering the dielectric constant and dielectric loss tangent when made into a prepreg or a printed wiring board, it is preferable to use a glass material containing B2O3 in a range of 15 to 40 mass % and SiO2 in a range of 45 to 60 mass % relative to the total amount of the long glass fibers, or a glass material containing SiO2 in a range of 98 to 100 mass % relative to the total amount of the long glass fibers.

[0020] In the present invention, the glass composition is measured by ICP optical emission spectroscopy. Specifically, the Si content and B content are obtained by melting a weighed glass cloth sample with sodium carbonate, dissolving it in dilute nitric acid to a constant volume, and measuring the obtained sample by ICP optical emission spectroscopy. The Fe content is obtained by dissolving a weighed glass cloth sample by an alkali dissolution method to a constant volume, and measuring the obtained sample by ICP optical emission spectroscopy. Furthermore, the Al content, Ca content, and Mg content are obtained by thermally decomposing a weighed glass cloth sample with sulfuric acid, nitric acid, and hydrogen fluoride, dissolving it in dilute nitric acid to a constant volume, and measuring the obtained sample by ICP optical emission spectroscopy. The ICP optical emission spectroscopy device can be an iCAP6300Duo manufactured by Thermo Fisher Scientific.

[0021] [Glass cloth] The glass cloth roll of the present invention is formed by winding a glass cloth having glass yarns as warp and weft.

[0022] In the present invention, the warp and weft constituting the glass cloth include glass yarns formed by bundling a plurality of long glass fibers. The average diameter of the long glass fibers is not particularly limited, but from the viewpoint of making the thickness of the glass cloth thinner, it is, for example, 2 to 7 μm, preferably 2.5 to 5.5 μm, more preferably 3 to 5.5 μm, even more preferably 3.2 to 5.5 μm, particularly preferably 3.2 to 4.2 μm, and even more preferably 3.5 to 4.1 μm. In addition, in the present invention, the number of long glass fibers constituting the warp and weft is not particularly limited, but from the viewpoint of making the thickness of the glass cloth thinner, it is, for example, 20 to 220, preferably 20 to 120, more preferably 20 to 55, and more preferably 30 to 55. Here, the average diameter and number of long glass fibers are measured and calculated as follows. That is, the glass cloth to be measured is cut into two pieces of 30 cm square, one for observing the warp threads and the other for observing the weft threads, and each is embedded in an epoxy-based cold embedding resin and hardened. Next, the glass cloth embedded in the epoxy-based cold embedding resin is polished to the extent that the warp threads or weft threads can be observed, and the average diameter is observed and measured at a magnification of 2000x and the number of threads at a magnification of 500x using an SEM. (1) Average diameter of long glass fibers (μm) Thirty warp threads and 30 weft threads are randomly selected, and the diameters (largest parts) of all the long glass fibers in the cross sections of the 30 warp threads and weft threads are measured and the arithmetic mean value is calculated to be the average diameter of the long glass fibers in the warp and weft threads. (2) Number of pieces Thirty warp threads and 30 weft threads are randomly selected, and the total length fiber counts of the 30 warp threads and weft threads are measured to calculate the arithmetic mean value, which is the number of long glass fibers in the warp and weft threads.

[0023] In the present invention, the counts of the warp and weft are not particularly limited, but from the viewpoint of making the thickness of the glass cloth thinner, for example, 0.5 to 12 tex is preferred, 0.5 to 5 tex is preferred, 0.5 to 3 tex is more preferred, 0.5 to 2 tex is even more preferred, 0.5 to 1.5 tex is particularly preferred, and 0.8 to 1.5 tex is even more preferred. The count of the warp in the glass cloth may be the same as or different from the count of the weft. In the present invention, the counts of the warp and weft in the glass cloth are values ​​measured and calculated according to the method specified in "7.1 Count" of the Japanese Industrial Standard JIS R 3420:2013 (General Test Method for Glass Fibers).

[0024] In the present invention, the weave density of the warp and weft is not particularly limited, but may be, for example, 40 / 25 mm or more and 160 / 25 mm or less, preferably 40 / 25 mm or more and 130 / 25 mm or less, more preferably 90 / 25 mm or more and 120 / 25 mm or less, and even more preferably 95 / 25 mm or more and 120 / 25 mm or less. The weave density of the warp in the glass cloth may be the same as or different from the weave density of the weft. Here, in the present invention, the weave density of the warp and weft is a value measured and calculated according to the method specified in "7.9 Density (weave density)" of the Japanese Industrial Standard JIS R 3420:2013 (General test method for glass fibers).

[0025] In the present invention, the weave of the glass cloth is not particularly limited, but examples thereof include plain weave, satin weave, twill weave, basket weave, rib weave, etc. Among these, plain weave is preferred.

[0026] In the present invention, the thickness of the glass cloth is not particularly limited, but may be, for example, 60 μm or less, preferably 30 μm or less, and more preferably 15 μm or less. The lower limit may be, for example, 5 μm or more, preferably 6 μm or more, more preferably 7 μm or more, and even more preferably 8 μm or more. Specific examples of the thickness of the glass cloth of the present invention include 5 μm or more and 60 μm or less, preferably 5 μm or more and 30 μm or less, more preferably 6 μm or more and 15 μm or less, even more preferably 7 μm or more and 15 μm or less, and even more preferably 8 μm or more and 15 μm or less. Here, the thickness of the glass cloth is measured using an electronic micrometer with a minimum display value of 0.001 mm in accordance with the B method specified in "7.10.1 Cloth thickness" of the Japanese Industrial Standard JIS R3420:2013 (general test method for glass fibers).

[0027] In the present invention, the mass of the glass cloth is not particularly limited, but is, for example, 60 g / m 2 The following are listed: 2 Less than 15 g / m is preferred. 2 The lower limit is, for example, 5 g / m 2 The above are listed, and 6g / m 2 More than 7g / m is preferable. 2 More preferably, the mass of the glass cloth in the present invention is 5 g / m 2 More than 60g / m 2 Less than 6g / m 2 More than 30g / m 2 Less than 7g / m, more preferably 2 More than 15g / m 2 Less than 8 g / m, more preferably 2 More than 15g / m 2 Here, the mass of the glass cloth is measured in accordance with the method specified in "7.2 Mass (mass) of cloth and mat" of Japanese Industrial Standard JIS R 3420:2013 (general test method for glass fibers).

[0028] In the present invention, the glass cloth may be treated with a surface treatment agent such as a silane coupling agent. Examples of the silane coupling agent applied as a surface treatment agent include a silane coupling agent having an amino group, a silane coupling agent having a vinyl group, a silane coupling agent having a phenyl group, a silane coupling agent having a glycidoxy group, a silane coupling agent having an isocyanate group, a silane coupling agent having a mercapto group, a silane coupling agent having a styryl group, and a silane coupling agent having a ureido group. In addition, in the present invention, the surface treatment agent applied to the glass cloth may include a resin, a surfactant, and the like.

[0029] [Glass cloth roll] The glass cloth roll of the present invention is formed by winding a glass cloth having glass yarns as warp and weft.

[0030] The glass cloth roll of the present invention has a glass cloth mass M (g / m 2 The tensile strength, expressed as the ratio (T / M) of the tensile strength T (N / 25mm) in the warp direction of the glass cloth to the tensile strength T (N / 25mm) in the warp direction of the glass cloth, is 3.8 or more and 6.0 or less. The upper limit of the tensile strength, 6.0, indicates that the glass cloth has been subjected to a heat cleaning treatment. That is, by performing a heat cleaning treatment, specifically, by placing a greige cloth wound in a roll shape around a metal core material in a heating furnace and heating and holding it at a temperature of about 400°C, the mechanical strength of the glass cloth is reduced. The tensile strength of the glass cloth that has not been subjected to a heat cleaning treatment exceeds 6.0, while the tensile strength of the glass cloth that has been subjected to a heat cleaning treatment is reduced and the tensile strength is 6.0 or less.

[0031] Furthermore, the glass cloth roll of the present invention has a tensile strength of 3.8 or more, expressed as the ratio (T / M) of the tensile strength T (N / 25mm) in the warp direction of the glass cloth. By having a tensile strength of 3.8 or more, it is possible to suppress a decrease in the tensile strength in the warp direction, and it is easy to suppress breakage during the production of prepregs even in thin glass cloths with a low mass. The ratio (T / M) can be 3.8 or more and 4.6 or less, or 4.4 or more and 5.7 or less, or 4.6 or more and 5.7 or less, or 4.4 or more and 5.1 or less.

[0032] In the glass cloth roll of the present invention, in order to set the tensile strength to 3.8 or more and 6.0 or less, a greige cloth is woven so that the ignition loss of the warp yarns is 2.5% by mass or more, and before being subjected to a heat cleaning treatment, this is subjected to a water washing treatment so that the ignition loss of the warp yarns is 2.0% by mass or less, and then, in a batch-type heat cleaning treatment method, the heat cleaning treatment is performed with a winding thickness of 80 mm or less, and the temperature and time of the heat cleaning are adjusted.

[0033] The tensile strength T (N / 25mm) in the warp direction is a value measured according to the method specified in "7.4.2 In the case of cloth" of the Japanese Industrial Standard JIS R 3420:2013 (General test method for glass fiber). Specifically, a test piece is taken from an arbitrary position of the outermost layer of a glass cloth roll, and a constant-speed extension type tensile tester is used, and the measurement conditions are a test piece length of 25 cm, a test piece width (width before the yarn is loosened from both ends) of 30 mm, a grip interval of 15 cm, a test piece width (width after the yarn is loosened from both ends) of 25 mm, and a constant-speed pulling speed of 200 mm / min. Then, the breaking strength is measured five times in the warp direction of the glass cloth, and the arithmetic mean value of the measured values ​​is taken as the tensile strength (N / 25mm) in the warp direction of the glass cloth. In the present invention, the outermost layer portion refers to a portion from the winding end of the outermost layer portion of the glass cloth roll to 100 m in the longitudinal direction (toward the innermost layer portion), and the innermost layer portion refers to a portion from the winding end of the innermost layer portion of the glass cloth roll to 100 m in the longitudinal direction (toward the outermost layer portion).

[0034] In the glass cloth roll of the present invention, the color difference ΔE between the outermost layer portion and the innermost layer portion is 0.1 or more and 1.5 or less, which makes it possible to reduce the difference in resin impregnation between the inner layer and the outer layer of the glass cloth roll when the glass cloth roll is made into a prepreg for printed circuit boards.

[0035] Specifically, the color difference ΔE can be measured as follows. That is, first, a glass cloth is drawn from the outermost layer and the innermost layer of a glass cloth roll, and cut into a square of 50 mm length and 50 mm width to prepare a measurement sample. The sampling position in the weft direction of the glass cloth roll is arbitrary. Next, a polyethylene bag (Shimojima Heiko Poly No. 803) having a thickness of 0.08 mm, width of 80 mm, and depth of 150 mm is prepared, and the prepared measurement samples are stacked in a plurality of sheets so that the measurement samples do not shift until the thickness reaches 4 mm, and are placed in the prepared polyethylene bag as is. Next, 100 g or more of a medium (for example, benzyl alcohol with a refractive index of 1.54 for a glass composition with a refractive index of 1.56, or a mixture of benzyl alcohol, methyl salicylate, or a mixture of 1 part glycerol and 2 parts water) is added to the polyethylene bag containing the stacked measurement samples, and the bag is sealed liquid-tight. Then, using a colorimeter, lightly press the color measuring part against the measurement sample to measure L*, a*, and b*. This is done for both the outermost layer measurement sample and the innermost layer measurement sample, and the color difference ΔE between the outermost layer and the innermost layer is calculated using the CIE1976 (L*a*b*) color difference formula.

[0036] From the viewpoint of more effectively suppressing a decrease in tensile strength in the warp direction and reducing the difference in resin impregnation property and heat resistance between the inner layer and the outer layer of the glass cloth roll when the glass cloth roll is made into a prepreg for printed circuit boards, the color difference ΔE is preferably 0.1 or more and 1.1 or less, and more preferably 0.2 or more and 0.7 or less.

[0037] The glass cloth roll of the present invention has an L* of 35 to 80 for the outermost layer and the innermost layer as determined when measuring the color difference ΔE, and from the viewpoint of both suppressing a decrease in tensile strength in the warp direction and reducing the difference in resin impregnation between the inner and outer layers of the glass cloth roll when used to form a prepreg for printed circuit boards, preferably 55 to 75, more preferably 64 to 70. The glass cloth roll of the present invention has an a* of -5 to 0 for the outermost layer and the innermost layer as determined when measuring the color difference ΔE, and from the viewpoint of both suppressing a decrease in tensile strength in the warp direction and reducing the difference in resin impregnation and heat resistance between the inner and outer layers of the glass cloth roll when used to form a prepreg for printed circuit boards, more preferably -0.5 to 0. In addition, the glass cloth roll of the present invention has b* of -12 to -5 for the outermost layer and the innermost layer as determined when measuring the above-mentioned color difference ΔE. From the viewpoint of simultaneously suppressing a decrease in tensile strength in the warp direction and reducing a difference in resin impregnation properties between the inner layer and the outer layer of the glass cloth roll when the glass cloth roll is made into a prepreg for printed circuit boards, the b* is preferably -12 to -7.8, and more preferably -9 to -7.8.

[0038] [Method of manufacturing glass cloth roll] Next, the method for producing the glass cloth roll of the present invention will be described.

[0039] A suitable method for manufacturing the glass cloth roll of the present invention includes: (1) a greige cloth preparation step of preparing a greige cloth having a warp thread loss on ignition of 2.5% by mass or more; (2) a water washing step of subjecting the prepared greige cloth to a water washing treatment so that the warp thread loss on ignition is 2.0% by mass or less; and (3) a heat cleaning step of winding the water-washed glass cloth into a roll having a thickness of 80 mm or less and subjecting the roll to a heat cleaning treatment.

[0040] (1) Preparation of grey cloth A grey cloth having a warp ignition loss of 2.5% by mass or more is prepared. This reduces damage to the warp during weaving and makes it easier to prevent a decrease in the tensile strength in the warp direction of the resulting glass cloth roll.

[0041] The green cloth can be obtained, for example, by the following process. (1-1) Spinning process Glass raw materials are melted in a glass melting furnace and drawn out as a plurality of long glass fibers, which are then bundled with a bundling agent to form a wound glass strand called a cake. (1-2) Yarn twisting process Glass strands are pulled from the cake and twisted in a twisting machine to form glass yarn. (1-3) Preparation process Glass yarn is used to prepare the warp yarn for the glass cloth through processes such as warping, sizing, and drawing. (1-4) Weaving process The prepared warp yarns and glass yarns as weft yarns are woven by an air jet loom or the like to produce a grey cloth.

[0042] The sizing agent applied to the long glass fibers in the spinning step is preferably one that is easily washed with water in the water washing treatment step described below, and may, for example, be one that contains starch. In the greige cloth, the ignition loss of the non-volatile components of the sizing agent is 0.5 to 2.0 mass%, and more preferably 0.8 to 1.5 mass%. In the present invention, the ignition loss is a value measured according to the method specified in "7.3.2 Ignition loss" of the Japanese Industrial Standard JIS R 3420:2013 (General test method for glass fibers).

[0043] The sizing agent applied by sizing in the preparation step is preferably one that is easily washed off in the water washing step described below, and may include one containing polyvinyl alcohol. In the greige cloth, the amount of nonvolatile components of the sizing agent adhering is 0.5 to 1.8% by mass, and more preferably 1.0 to 1.8% by mass. The amount of nonvolatile components of the sizing agent adhering can be determined by subtracting the ignition loss of the glass yarn before sizing (the ignition loss of the nonvolatile components of the bundling agent) from the ignition loss of the warp yarn of the greige cloth described below (the ignition loss before the water washing treatment).

[0044] The ignition loss of the warp yarn of the greige cloth is more preferably 2.5 to 2.8% by mass, and even more preferably 2.5 to 2.6% by mass. The ignition loss of the weft yarn of the greige cloth is 0.5 to 2.0% by mass, and more preferably 0.8 to 1.5% by mass. The ignition loss of the warp yarn and the weft yarn of the greige cloth is a value measured by taking the warp yarn and the weft yarn from the greige cloth, respectively, according to the method specified in "7.3.2 Ignition loss" of the Japanese Industrial Standard JIS R 3420:2013 (General test method for glass fibers).

[0045] (2) Water washing process The prepared grey cloth is washed with water so that the ignition loss of the warp yarn is 2.0% by mass or less, whereby the color difference ΔE between the outermost layer and the innermost layer in the glass cloth roll can be 0.1 to 1.5.

[0046] The water washing treatment is not particularly limited as long as the ignition loss can be 2.0% by mass or less. For example, a method using a high-pressure water spray, a method of continuously immersing a glass cloth in a water tank and washing it with water, a method of using ultrasonic energy by installing an ultrasonic oscillator in a water tank, or a vibro washer method in which a glass cloth is moved along a rotating cylinder having a large number of holes and high-pressure water is sprayed from the holes to wash off the sizing agent, etc. can be mentioned. The temperature of the water can be appropriately set, and can be, for example, 15 to 100°C. When performing the water washing treatment using a high-pressure water spray, the spray pressure can be 0.1 to 3.0 MPa.

[0047] After the water washing treatment step, it is preferable to dry the water-washed glass cloth at an atmospheric temperature of 100 to 150° C. for a time of 60 to 300 seconds.

[0048] After the water washing process, the glass cloth roll is dried as necessary, wound into a roll, and subjected to the heat cleaning process described below. An iron core is used as the winding core when winding into a roll. The diameter of the iron core is not particularly limited, but may be, for example, about 400 to 600 mm, and preferably about 450 to 550 mm.

[0049] (3) Heat cleaning process The glass cloth that has been subjected to the water washing treatment is wound into a roll having a thickness of 80 mm or less, and is then subjected to a heat cleaning treatment, whereby the color difference ΔE between the outermost layer and the innermost layer in the glass cloth roll can be made 0.1 or more and 1.5 or less.

[0050] As described above, when the heat cleaning treatment is performed by the batch method, the glass cloth is wound around an iron core in a roll shape, so that the inner layer part of the glass cloth roll subjected to the heat cleaning treatment is likely to be insufficient in air supply from the outside, and is heated in a state of insufficient oxygen. As a result, after the heat cleaning treatment, the inner layer part is likely to have a lower degree of removal of organic components attached to the glass cloth, such as a bundling agent, than the outer layer part of the glass cloth roll subjected to the heat cleaning treatment. In the manufacturing method of the glass cloth roll of the present invention, the method includes a water washing treatment step of washing the prepared greige cloth with water so that the ignition loss of the warp yarn is 2.0 mass% or less, and a heat cleaning treatment step of winding the glass cloth subjected to the water washing treatment into a roll shape with a thickness of 80 mm or less, more preferably 15 to 40 mm, and performing a heat cleaning treatment, thereby making it possible to make the above color difference ΔE 0.1 to 1.5, and to reduce the difference in resin impregnation and heat resistance between the inner layer and the outer layer of the glass cloth roll when it is made into a prepreg for printed circuit boards. In addition, when a continuous deoiling method is used in which the glass cloth is continuously run in the warp direction through a furnace having an atmospheric temperature of, for example, 400°C or higher and wound up instead of the batch method, the degree of removal of organic components adhering to the glass cloth, such as the bundling agent, becomes uniform between the outer layer and the inner layer of the wound glass cloth roll, and it is not possible to make ΔE 0.1 or more.

[0051] The density of the glass cloth roll in the heat cleaning process is 0.7 to 1.3 g / cm 3 and 0.8 to 1.2 g / cm 3 are preferred.

[0052] The atmospheric temperature in the heat cleaning treatment step is, for example, 350 to 500° C., and preferably 400 to 450° C. The heat cleaning treatment time is, for example, 18 to 48 hours, and preferably 22 to 35 hours.

[0053] Other processes The method for producing a glass cloth roll of the present invention may include, after the heat cleaning treatment step, a surface treatment step of treating the heat-cleaned glass cloth with a silane coupling agent in order to improve the adhesion between the matrix resin and the long glass fibers in the prepreg production, and a fiber-spreading step of widening the width of the warp and weft of the glass cloth. The surface treatment step and the fiber-spreading step may be performed in any order, or may be performed simultaneously. The roll that has been subjected to the heat cleaning treatment step may be rewound by the other steps. That is, as a result of the rewinding, the part that was the outermost layer part in the heat cleaning treatment step may be located in the innermost layer part in the final glass cloth roll product, and the part that was the innermost layer part in the heat cleaning treatment step may be located in the outermost layer part in the final glass cloth roll product. However, even if the roll is rewound, the color difference ΔE is calculated as a positive value according to the "CIE1976 (L*a*b*) color difference formula", so that the value is not affected by rewinding. EXAMPLES

[0054] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the examples.

[0055] <Example 1> 1. Preparation of grey cloth The glass yarns prepared for the warp and weft were made of E-glass, had an average long glass fiber diameter of 4.5 μm, contained 100 long glass fibers, had a twist of 1.0Z, and had a count of 4.2 tex. The glass yarns had a sizing agent containing starch applied to the surfaces of the long glass fibers, and had an ignition loss of 1.0% by mass.

[0056] A sizing agent containing polyvinyl alcohol was prepared. The solid content of the sizing agent was 3.5% by mass. The prepared warp yarn and sizing agent were used to prepare a beam by warping, sizing, and drawing. The beamed warp yarn was set on an air jet loom, and the prepared weft yarn was used to weave a plain weave structure, which was then wound up to obtain a greige cloth. The ignition loss of the greige cloth warp yarn was 2.5% by mass.

[0057] 2. Water washing process The greige cloth was subjected to a water washing treatment so that the ignition loss of the warp yarns was 2.0% by mass or less. Specifically, the greige cloth was pulled out from the roll on which it was wound, and was continuously washed with water using a high-pressure water spray at a pressure of 2.4 MPa, dried at a drying temperature of 135°C for 180 seconds, and wound around a cylindrical iron core with a diameter of 485 mm. The ignition loss of the warp yarns of the greige cloth after the water washing treatment was 2.0% by mass, the thickness of the roll wound around the iron core was 72 mm, and the density of the glass cloth roll was 0.92 g / cm 3 The width of the wound glass cloth was 1,330 mm and the length was 5,000 m.

[0058] 3.Heat cleaning process The glass cloth roll was washed with water, dried, and wound up, and placed in a batch oven and subjected to a heat cleaning treatment at an atmospheric temperature of 400° C. for 35 hours. The glass cloth roll that had been subjected to the heat cleaning treatment was then allowed to stand for 24 hours in an environment with an atmospheric temperature of 23° C. and cooled. The ignition loss after the heat cleaning treatment was 0.08% by mass.

[0059] 4. Surface treatment process and fiber opening process A glass cloth was drawn out from the glass cloth roll that had been subjected to the above heat cleaning treatment, and a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation) was adjusted to a concentration of 10 g / L and applied to the glass cloth. The glass cloth was then squeezed with a Padder roll, dried and cured at 120° C. for 1 minute, and wound into a roll. Next, the glass cloth was drawn out from the wound roll, subjected to a fiber-opening treatment using a water flow process at a pressure of 1.0 MPa, dried, and wound into a roll to obtain a glass cloth roll of the present invention. The physical properties of the obtained glass cloth roll are shown in Table 1. The ignition loss of the glass cloth roll was 0.14% by mass, and the length was 5000 m.

[0060] <Example 2> 1. Preparation of grey cloth The glass yarns prepared for the warp and weft were made of E-glass, had an average long glass fiber diameter of 4.5 μm, contained 100 long glass fibers, had a twist of 1.0Z, and had a count of 4.2 tex. The glass yarns had a sizing agent containing starch applied to the surfaces of the long glass fibers, and had an ignition loss of 1.0% by mass.

[0061] A sizing agent containing polyvinyl alcohol was prepared. The solid content of the sizing agent was 3.5% by mass. The prepared warp yarn and sizing agent were used to prepare a beam by warping, sizing, and drawing. The beamed warp yarn was set on an air jet loom, and the prepared weft yarn was used to weave a plain weave structure, which was then wound up to obtain a greige cloth. The ignition loss of the greige cloth warp yarn was 2.5% by mass.

[0062] 2. Water washing process The greige cloth was subjected to a water washing treatment so that the ignition loss of the warp yarns was 2.0% by mass or less. Specifically, the greige cloth was pulled out from the roll on which it was wound, and was continuously washed with water using a high-pressure water spray at a pressure of 2.4 MPa, dried at a drying temperature of 135°C for 180 seconds, and wound around a cylindrical iron core with a diameter of 485 mm. The ignition loss of the warp yarns of the greige cloth after the water washing treatment was 2.0% by mass, the thickness of the roll wound around the iron core was 38 mm, and the density of the glass cloth roll was 0.92 g / cm 3 The width of the wound glass cloth was 1,330 mm and the length was 2,500 m.

[0063] 3.Heat cleaning process The glass cloth roll was washed with water, dried, and wound up, and placed in a batch oven and subjected to a heat cleaning treatment at an atmospheric temperature of 400° C. for 35 hours. The glass cloth roll that had been subjected to the heat cleaning treatment was then allowed to stand for 24 hours in an environment with an atmospheric temperature of 24° C. and cooled. The ignition loss after the heat cleaning treatment was 0.08% by mass.

[0064] 4. Surface treatment process and fiber opening process A glass cloth was drawn out from the glass cloth roll that had been subjected to the above heat cleaning treatment, and a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation) was adjusted to a concentration of 10 g / L and applied to the glass cloth. The glass cloth was then squeezed with a Padder roll, dried and cured at 120° C. for 1 minute, and wound into a roll. Next, the glass cloth was drawn out from the wound roll, subjected to a fiber-opening treatment using a water flow process at a pressure of 1.0 MPa, dried, and wound into a roll to obtain a glass cloth roll of the present invention. The physical properties of the obtained glass cloth roll are shown in Table 1. The ignition loss of the glass cloth roll was 0.14% by mass, and the length was 2500 m.

[0065] <Example 3> 1. Preparation of grey cloth The glass yarns prepared for the warp and weft were made of E-glass, had an average long glass fiber diameter of 5.0 μm, 200 long glass fibers, a twist number of 1.0Z, and a yarn count of 11.2 tex. The glass yarns had a sizing agent containing starch applied to the surfaces of the long glass fibers, and had an ignition loss of 1.0% by mass.

[0066] A sizing agent containing polyvinyl alcohol was prepared. The solid content of the sizing agent was 5.0% by mass. The prepared warp yarn and sizing agent were used to prepare a beam by warping, sizing, and drawing. The beamed warp yarn was set on an air jet loom, and the prepared weft yarn was used to weave a plain weave structure, which was then wound up to obtain a greige cloth. The ignition loss of the greige cloth warp yarn was 2.5% by mass.

[0067] 2. Water washing process The greige cloth was subjected to a water washing treatment so that the ignition loss of the warp yarns was 2.0% by mass or less. Specifically, the greige cloth was pulled out from the roll on which it was wound, and was continuously washed with water using a high-pressure water spray at a pressure of 2.4 MPa, dried at a drying temperature of 135°C for 180 seconds, and wound around a cylindrical iron core with a diameter of 485 mm. The ignition loss of the warp yarns of the greige cloth after the water washing treatment was 2.0% by mass, the thickness of the roll wound around the iron core was 63 mm, and the density of the glass cloth roll was 1.11 g / cm 3 The width of the wound glass cloth was 1,330 mm and the length was 2,500 m.

[0068] 3.Heat cleaning process The glass cloth roll was washed with water, dried, and wound up, and placed in a batch oven and subjected to a heat cleaning treatment at an atmospheric temperature of 135° C. for 35 hours. The glass cloth roll that had been subjected to the heat cleaning treatment was then allowed to stand for 24 hours in an environment with an atmospheric temperature of 24° C. to cool. The ignition loss after the heat cleaning treatment was 0.08% by mass.

[0069] 4. Surface treatment process and fiber opening process A glass cloth was drawn out from the glass cloth roll that had been subjected to the above heat cleaning treatment, and a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation) was adjusted to a concentration of 10 g / L and applied to the glass cloth. The glass cloth was then squeezed with a Padder roll, dried and cured at 120° C. for 1 minute, and wound into a roll. Next, the glass cloth was drawn out from the wound roll, subjected to a fiber-opening treatment using a water flow process at a pressure of 1.0 MPa, dried, and wound into a roll to obtain a glass cloth roll of the present invention. The physical properties of the obtained glass cloth roll are shown in Table 1. The ignition loss of the glass cloth roll was 0.14% by mass, and the length was 2500 m.

[0070] <Example 4> 1. Preparation of grey cloth The glass yarns prepared for the warp and weft were made of E-glass, had an average long glass fiber diameter of 4.0 μm, contained 50 long glass fibers, had a twist of 0.5Z, and had a count of 1.7 tex. The glass yarns had a sizing agent containing starch applied to the surfaces of the long glass fibers, and had an ignition loss of 1.0% by mass.

[0071] A sizing agent containing polyvinyl alcohol was prepared. The solid content of the sizing agent was 2.4% by mass. The prepared warp yarn and sizing agent were used to prepare a beam by warping, sizing, and drawing. The beamed warp yarn was set on an air jet loom, and the prepared weft yarn was used to weave a plain weave structure, which was then wound up to obtain a greige cloth. The ignition loss of the greige cloth warp yarn was 2.5% by mass.

[0072] 2. Water washing process The greige cloth was subjected to a water washing treatment so that the ignition loss of the warp yarns was 2.0% by mass or less. Specifically, the greige cloth was pulled out from the roll on which it was wound, and was continuously washed with water using a high-pressure water spray at a pressure of 1.4 MPa, dried at a drying temperature of 135°C for 180 seconds, and wound around a cylindrical iron core with a diameter of 485 mm. The ignition loss of the warp yarns of the greige cloth after the water washing treatment was 2.0% by mass, the thickness of the roll wound around the iron core was 19 mm, and the density of the glass cloth roll was 0.80 g / cm 3 The width of the wound glass cloth was 1,330 mm and the length was 2,000 m.

[0073] 3.Heat cleaning process The glass cloth roll was washed with water, dried, and wound up, and placed in a batch oven and subjected to a heat cleaning treatment at an atmospheric temperature of 400° C. for 35 hours. The glass cloth roll that had been subjected to the heat cleaning treatment was then allowed to stand for 24 hours in an environment with an atmospheric temperature of 24° C. and cooled. The ignition loss after the heat cleaning treatment was 0.08% by mass.

[0074] 4. Surface treatment process and fiber opening process A glass cloth was drawn out from the glass cloth roll that had been subjected to the above heat cleaning treatment, and a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation) was adjusted to a concentration of 10 g / L and applied to the glass cloth. The glass cloth was then squeezed with a Padder roll, dried and cured at 120° C. for 1 minute, and wound into a roll. Next, the glass cloth was drawn out from the wound roll, subjected to a fiber-opening treatment using a water flow process at a pressure of 1.0 MPa, dried, and wound into a roll to obtain a glass cloth roll of the present invention. The physical properties of the obtained glass cloth roll are shown in Table 1. The ignition loss of the glass cloth roll was 0.14% by mass, and the length was 2000 m.

[0075] <Comparative Example 1> 1. Preparation of grey cloth The glass yarns prepared for the warp and weft were made of E-glass, had an average long glass fiber diameter of 4.5 μm, contained 100 long glass fibers, had a twist of 1.0Z, and had a count of 4.2 tex. The glass yarns had a sizing agent containing starch applied to the surfaces of the long glass fibers, and had an ignition loss of 1.0% by mass.

[0076] A sizing agent containing polyvinyl alcohol was prepared. The solid content of the sizing agent was 3.5% by mass. The prepared warp yarn and sizing agent were used to prepare a beam by warping, sizing, and drawing. The beamed warp yarn was set on an air jet loom, and the prepared weft yarn was used to weave a plain weave structure, which was then wound up to obtain a greige cloth. The ignition loss of the greige cloth warp yarn was 2.5% by mass.

[0077] 2. Water washing process The greige cloth was subjected to a water washing treatment so that the ignition loss of the warp yarns was 2.0% by mass or less. Specifically, the greige cloth was pulled out from the roll on which it was wound, and was continuously washed with water using a high-pressure water spray at a pressure of 2.4 MPa, dried at a drying temperature of 135°C for 180 seconds, and wound around a cylindrical iron core with a diameter of 485 mm. The ignition loss of the warp yarns of the greige cloth after the water washing treatment was 2.0% by mass, the winding thickness of the roll wound around the iron core was 84 mm, and the density of the glass cloth roll was 0.92 g / cm 3 The width of the wound glass cloth was 1,330 mm and the length was 6,000 m.

[0078] 3.Heat cleaning process The glass cloth roll was washed with water, dried, and wound up, and placed in a batch oven and subjected to a heat cleaning treatment at an atmospheric temperature of 400° C. for 35 hours. The glass cloth roll that had been subjected to the heat cleaning treatment was then allowed to stand for 24 hours in an environment with an atmospheric temperature of 24° C. and cooled. The ignition loss after the heat cleaning treatment was 0.10% by mass.

[0079] 4. Surface treatment process and fiber opening process A glass cloth was pulled out from the glass cloth roll that had been subjected to the above heat cleaning treatment, and a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation) was adjusted to a concentration of 10 g / L and applied to the glass cloth. The glass cloth was then squeezed with a Padder roll, dried and cured at 120° C. for 1 minute, and wound into a roll. Next, the glass cloth was pulled out from the wound roll, subjected to a fiber-opening treatment using a water flow process at a pressure of 1.0 MPa, dried, and wound into a roll to obtain a glass cloth roll of a comparative example. The physical properties of the obtained glass cloth roll are shown in Table 1. The ignition loss of the glass cloth roll was 0.17% by mass, and the length was 6000 m.

[0080] <Comparative Example 2> 1. Preparation of grey cloth The glass yarns prepared for the warp and weft were made of E-glass, had an average long glass fiber diameter of 5.0 μm, 200 long glass fibers, a twist number of 1.0Z, and a yarn count of 11.2 tex. The glass yarns had a sizing agent containing starch applied to the surfaces of the long glass fibers, and had an ignition loss of 1.0% by mass.

[0081] A sizing agent containing polyvinyl alcohol was prepared. The solid content of the sizing agent was 3.5% by mass. The prepared warp yarn and sizing agent were used to prepare a beam by warping, sizing, and drawing. The beamed warp yarn was set on an air jet loom, and the prepared weft yarn was used to weave a plain weave structure, which was then wound up to obtain a greige cloth. The ignition loss of the greige cloth warp yarn was 2.5% by mass.

[0082] 2. Water washing process The greige cloth was subjected to a water washing treatment so that the ignition loss of the warp yarns was 2.0% by mass or less. Specifically, the greige cloth was pulled out from the roll on which it was wound, and was continuously washed with water using a high-pressure water spray at a pressure of 2.4 MPa, dried at a drying temperature of 135°C for 180 seconds, and wound around a cylindrical iron core with a diameter of 485 mm. The ignition loss of the warp yarns of the greige cloth after the water washing treatment was 2.0% by mass, the thickness of the roll wound around the iron core was 114 mm, and the density of the glass cloth roll was 1.11 g / cm 3 The width of the wound glass cloth was 1,330 mm and the length was 5,000 m.

[0083] 3.Heat cleaning process The glass cloth roll was washed with water, dried, and wound up, and placed in a batch oven and subjected to a heat cleaning treatment at an atmospheric temperature of 400° C. for 35 hours. The glass cloth roll that had been subjected to the heat cleaning treatment was then allowed to stand for 24 hours in an environment with an atmospheric temperature of 24° C. and cooled. The ignition loss after the heat cleaning treatment was 0.10% by mass.

[0084] 4. Surface treatment process and fiber opening process A glass cloth was pulled out from the glass cloth roll that had been subjected to the above heat cleaning treatment, and a surface treatment agent, a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation), was adjusted to a concentration of 10 g / L and applied to the glass cloth. The glass cloth was then squeezed with a padder roll, dried and cured at 120° C. for 1 minute, and wound into a roll. Next, the glass cloth was pulled out from the wound roll, subjected to a fiber-opening treatment using a water flow process at a pressure of 1.0 MPa, dried, and wound into a roll to obtain a glass cloth roll of a comparative example. The physical properties of the obtained glass cloth roll are shown in Table 1. The ignition loss of the glass cloth roll was 0.17% by mass, and the length was 5000 m.

[0085] <Comparative Example 3> 1. Preparation of grey cloth The glass yarns prepared for the warp and weft were made of E-glass, had an average long glass fiber diameter of 4.5 μm, contained 100 long glass fibers, had a twist of 1.0Z, and had a count of 4.2 tex. The glass yarns had a sizing agent containing starch applied to the surfaces of the long glass fibers, and had an ignition loss of 1.0% by mass.

[0086] A sizing agent containing polyvinyl alcohol was prepared. The solid content concentration of the sizing agent was 4.0% by mass. The prepared warp yarn and sizing agent were used to prepare a beam by warping, sizing, and drawing, and the beamed warp yarn was set on an air jet loom, and the prepared weft yarn was used to weave a plain weave structure, which was then wound up to obtain a greige cloth. The ignition loss of the warp yarn of the greige cloth was 3.0% by mass.

[0087] 2. Water washing process The greige cloth was subjected to a water washing treatment. Specifically, the greige cloth was pulled out from the roll on which it was wound, and was continuously subjected to a water washing treatment with a high-pressure water spray at a pressure of 2.4 MPa, and was dried at a drying temperature of 135°C for 180 seconds, and then wound around a cylindrical iron core with a diameter of 485 mm. After the water washing treatment, the ignition loss of the warp yarn of the greige cloth was 2.5% by mass, the winding thickness of the roll wound around the iron core was 72 mm, and the density of the glass cloth roll was 0.92 g / cm 3 The width of the wound glass cloth was 1,330 mm and the length was 5,000 m.

[0088] 3.Heat cleaning process The glass cloth roll was washed with water, dried, and wound up, and placed in a batch oven and subjected to a heat cleaning treatment at an atmospheric temperature of 400° C. for 35 hours. The glass cloth roll that had been subjected to the heat cleaning treatment was then allowed to stand for 24 hours in an environment with an atmospheric temperature of 24° C. and cooled. The ignition loss after the heat cleaning treatment was 0.15% by mass.

[0089] 4. Surface treatment process and fiber opening process A glass cloth was pulled out from the glass cloth roll that had been subjected to the above heat cleaning treatment, and a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation) was adjusted to a concentration of 10 g / L and applied to the glass cloth. The glass cloth was squeezed with a padder roll, then dried and cured at 120° C. for 1 minute, and wound into a roll. Next, the glass cloth was pulled out from the wound roll, subjected to a fiber-opening treatment using a water flow process at a pressure of 1.0 MPa, dried, and wound into a roll to obtain a glass cloth roll of a comparative example. The physical properties of the obtained glass cloth roll are shown in Table 1. The ignition loss of the glass cloth roll was 0.20 mass % and the length was 5000 m.

[0090] <Comparative Example 4> 1. Preparation of grey cloth The glass yarns prepared for the warp and weft were made of E-glass, had an average long glass fiber diameter of 4.5 μm, contained 100 long glass fibers, had a twist of 1.0Z, and had a count of 4.2 tex. The glass yarns had a sizing agent containing starch applied to the surfaces of the long glass fibers, and had an ignition loss of 1.0% by mass.

[0091] A sizing agent containing polyvinyl alcohol was prepared. The solid content concentration of the sizing agent was 4.0% by mass. The prepared warp yarn and sizing agent were used to prepare a beam by warping, sizing, and drawing, and the beamed warp yarn was set on an air jet loom, and the prepared weft yarn was used to weave a plain weave structure, which was then wound up to obtain a greige cloth. The ignition loss of the warp yarn of the greige cloth was 3.0% by mass.

[0092] 2. Water washing process The greige cloth was subjected to a water washing treatment. Specifically, the greige cloth was pulled out from the roll on which it was wound, and was continuously subjected to a water washing treatment with a high-pressure water spray at a pressure of 2.4 MPa, and was dried at a drying temperature of 135°C for 180 seconds, and then wound around a cylindrical iron core with a diameter of 485 mm. After the water washing treatment, the ignition loss of the warp yarn of the greige cloth was 2.5% by mass, the winding thickness of the roll wound around the iron core was 38 mm, and the density of the glass cloth roll was 0.92 g / cm 3 The width of the wound glass cloth was 1,330 mm and the length was 2,500 m.

[0093] 3.Heat cleaning process The glass cloth roll was washed with water, dried, and wound up, and placed in a batch oven and subjected to a heat cleaning treatment at an atmospheric temperature of 400° C. for 35 hours. The glass cloth roll that had been subjected to the heat cleaning treatment was then allowed to stand for 24 hours in an environment with an atmospheric temperature of 24° C. and cooled. The ignition loss after the heat cleaning treatment was 0.15% by mass.

[0094] 4. Surface treatment process and fiber opening process A glass cloth was pulled out from the glass cloth roll that had been subjected to the above heat cleaning treatment, and a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation) was adjusted to a concentration of 10 g / L and applied to the glass cloth. The glass cloth was then squeezed with a padder roll, dried and cured at 120° C. for 1 minute, and wound into a roll. Next, the glass cloth was pulled out from the wound roll, subjected to a fiber-opening treatment using a water flow process at a pressure of 1.0 MPa, dried, and wound into a roll to obtain a glass cloth roll of a comparative example. The physical properties of the obtained glass cloth roll are shown in Table 1. The ignition loss of the glass cloth roll was 0.20% by mass, and the length was 2500 m.

[0095] <Comparative Example 5> 1. Preparation of grey cloth The glass yarns prepared for the warp and weft were made of E-glass, had an average long glass fiber diameter of 4.5 μm, contained 100 long glass fibers, had a twist of 1.0Z, and had a count of 4.2 tex. The glass yarns had a sizing agent containing starch applied to the surfaces of the long glass fibers, and had an ignition loss of 1.0% by mass.

[0096] A sizing agent containing polyvinyl alcohol was prepared. The solid content concentration of the sizing agent was 3.0% by mass. The prepared warp yarn and sizing agent were used to prepare a beam by warping, sizing, and drawing, and the beamed warp yarn was set on an air jet loom, and the prepared weft yarn was used to weave a plain weave structure, which was then wound up to obtain a greige cloth. The ignition loss of the greige cloth warp yarn was 1.5% by mass.

[0097] 2. Water washing process The greige cloth was subjected to a water washing treatment. Specifically, the greige cloth was pulled out from the roll on which it was wound, and was continuously subjected to a water washing treatment with a high-pressure water spray at a pressure of 2.4 MPa, and was dried at a drying temperature of 135°C for 180 seconds, and then wound around a cylindrical iron core with a diameter of 485 mm. After the water washing treatment, the ignition loss of the warp yarn of the greige cloth was 1.0 mass%, the winding thickness of the roll wound around the iron core was 82 mm, and the density of the glass cloth roll was 0.92 g / cm 3 The width of the wound glass cloth was 1,330 mm and the length was 5,900 m.

[0098] 3.Heat cleaning process The glass cloth roll was washed with water, dried, and wound up, and placed in a batch oven and subjected to a heat cleaning treatment at an atmospheric temperature of 400° C. for 35 hours. The glass cloth roll that had been subjected to the heat cleaning treatment was then allowed to stand for 24 hours in an environment with an atmospheric temperature of 24° C. and cooled. The ignition loss after the heat cleaning treatment was 0.10% by mass.

[0099] 4. Surface treatment process and fiber opening process A glass cloth was pulled out from the glass cloth roll that had been subjected to the above heat cleaning treatment, and a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation) was adjusted to a concentration of 10 g / L and applied to the glass cloth. The glass cloth was then squeezed with a padder roll, dried and cured at 120° C. for 1 minute, and wound into a roll. Next, the glass cloth was pulled out from the wound roll, subjected to a fiber-opening treatment using a water flow process at a pressure of 1.0 MPa, dried, and wound into a roll to obtain a glass cloth roll of a comparative example. The physical properties of the obtained glass cloth roll are shown in Table 1. The ignition loss of the glass cloth roll was 0.17% by mass, and the length was 5900 m.

[0100] <Comparative Example 6> 1. Preparation of grey cloth The glass yarns prepared for the warp and weft were made of E-glass, had an average long glass fiber diameter of 4.0 μm, contained 50 long glass fibers, had a twist of 0.5Z, and had a count of 1.7 tex. The glass yarns had a sizing agent containing starch applied to the surfaces of the long glass fibers, and had an ignition loss of 1.0% by mass.

[0101] A sizing agent containing polyvinyl alcohol was prepared. The solid content concentration of the sizing agent was 2.4% by mass. The prepared warp yarns and sizing agent were used to prepare a beam by warping, sizing, and drawing. The beamed warp yarns were set on an air jet loom, and the prepared weft yarns were used to weave a plain weave. The weft yarns were then wound around a cylindrical iron core with a diameter of 485 mm to obtain a greige cloth. The ignition loss of the greige cloth warp yarns was 2.5% by mass, the thickness of the roll wound around the iron core was 19 mm, and the density of the glass cloth roll was 0.80 g / cm. 3 The width of the wound glass cloth was 1,330 mm and the length was 2,000 m.

[0102] 2.Heat cleaning process Without washing with water, the greige cloth roll was placed in a batch oven and subjected to heat cleaning at an atmospheric temperature of 400° C. for 35 hours. The glass cloth roll subjected to heat cleaning was then allowed to stand for 24 hours in an environment with an atmospheric temperature of 24° C. to cool. The ignition loss after the heat cleaning was 0.15% by mass.

[0103] 3. Surface treatment process and fiber opening process A glass cloth was pulled out from the glass cloth roll that had been subjected to the above heat cleaning treatment, and a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation) was adjusted to a concentration of 10 g / L and applied to the glass cloth. The glass cloth was then squeezed with a padder roll, dried and cured at 120° C. for 1 minute, and wound into a roll. Next, the glass cloth was pulled out from the wound roll, subjected to a fiber-opening treatment using a water flow process at a pressure of 1.0 MPa, dried, and wound into a roll to obtain a glass cloth roll of a comparative example. The physical properties of the obtained glass cloth roll are shown in Table 1. The ignition loss of the glass cloth roll was 0.20% by mass, and the length was 2000 m.

[0104] <Comparative Example 7> 1. Preparation of grey cloth The glass yarns prepared for the warp and weft were made of E-glass, had an average long glass fiber diameter of 5.0 μm, 200 long glass fibers, a twist number of 1.0Z, and a yarn count of 11.2 tex. The glass yarns had a sizing agent containing starch applied to the surfaces of the long glass fibers, and had an ignition loss of 1.0% by mass.

[0105] A sizing agent containing polyvinyl alcohol was prepared. The solid content concentration of the sizing agent was 5.0% by mass. The prepared warp yarns and sizing agent were used to prepare a beam by warping, sizing, and drawing. The beamed warp yarns were set on an air jet loom, and the prepared weft yarns were used to weave a plain weave. The weft yarns were then wound around a cylindrical iron core with a diameter of 485 mm to obtain a greige cloth. The ignition loss of the greige cloth warp yarns was 2.5% by mass, the thickness of the roll wound around the iron core was 114 mm, and the density of the glass cloth roll was 1.11 g / cm. 3 The width of the wound glass cloth was 1,330 mm and the length was 5,000 m.

[0106] 3.Heat cleaning process Without washing with water, the greige cloth roll was placed in a batch oven and subjected to heat cleaning at an atmospheric temperature of 400° C. for 35 hours. The glass cloth roll subjected to heat cleaning was then allowed to stand for 24 hours in an environment with an atmospheric temperature of 24° C. to cool. The ignition loss after the heat cleaning was 0.15% by mass.

[0107] 4. Surface treatment process and fiber opening process A glass cloth was pulled out from the glass cloth roll that had been subjected to the above heat cleaning treatment, and a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation) was adjusted to a concentration of 10 g / L and applied to the glass cloth. The glass cloth was squeezed with a padder roll, then dried and cured at 120° C. for 1 minute, and wound into a roll. Next, the glass cloth was pulled out from the wound roll, subjected to a fiber-opening treatment using a water flow process at a pressure of 1.0 MPa, dried, and wound into a roll to obtain a glass cloth roll of a comparative example. The physical properties of the obtained glass cloth roll are shown in Table 1. The ignition loss of the glass cloth roll was 0.20 mass % and the length was 5000 m.

[0108] <Method of measuring physical properties> 1. Average diameter (μm) and number (of fibers) of long glass fibers in glass yarn Using the prepared glass yarn, the average diameter of the long glass fiber was measured and calculated according to the method specified in the B method (cross-sectional method) of "7.6 Single fiber diameter" of "General test method for glass fiber" of the Japanese Industrial Standard JIS R 3420:2013. Specifically, the prepared glass yarn was embedded in an epoxy-based cold embedding resin (manufactured by Struers, product name Epoxy Resin Specifix-40) and cured to obtain a cured product. Next, the cured product was polished to such an extent that the glass yarn embedded in the epoxy-based cold embedding resin could be observed, and the average diameter was observed and measured at a magnification of 2000 times and the number of fibers was observed and measured at a magnification of 500 times using a scanning electron microscope (SEM) (manufactured by JEOL Ltd., product name JSM-6390A). Thirty glass yarns were randomly selected, and the diameters (largest part) of all the long glass fibers in the 30 glass yarns in the cross section were measured to calculate the arithmetic mean value, which was used as the average diameter of the long glass fibers in the glass yarn. The number of long glass fibers (arithmetic mean value) of the glass yarn was measured in measuring the average diameter of the long glass fibers.

[0109] 2. Glass yarn count (tex) Using the prepared glass yarn, measurements and calculations were performed according to the method specified in "7.1 Count" of the Japanese Industrial Standard JIS R 3420: 2013 (General Test Method for Glass Fibers).

[0110] 3. Ignition loss of glass yarn (mass%) Using the prepared glass yarn, measurements and calculations were made according to the method specified in "7.3.2 Ignition loss" of the Japanese Industrial Standard JIS R 3420:2013 (general test method for glass fibers).

[0111] 4. Ignition loss (mass%) of warp yarn of grey cloth before and after water washing treatment Warp threads were taken from the grey cloth before and after the water washing treatment, and were measured and calculated according to the method specified in "7.3.2 Ignition loss" of the Japanese Industrial Standard JIS R 3420:2013 (General test method for glass fibers). Specifically, 1g or more of warp threads were taken from the grey cloth, dried at 105°C for 1 hour, then placed in a desiccator to cool to room temperature and its mass (M1) was measured. This was heated for 30 minutes in a muffle furnace maintained at 625±20°C, then placed in a desiccator to cool to room temperature, its mass (M2) was measured and calculated using the following formula. C = (M1-M2) / M1 x 100 C = Ignition loss of the test piece (mass%)

[0112] 5. Thickness of glass cloth roll before heat cleaning treatment (mm) Fig. 1 is a schematic diagram for explaining the measurement of the winding thickness of a glass cloth roll 1 wound around an iron core 2 before the heat cleaning treatment, and is a schematic diagram showing an end face (corresponding to the bottom part of the cylindrical shape) of the glass cloth roll viewed from a planar direction. The winding thickness of the glass cloth roll before the heat cleaning treatment shown in Fig. 1 was measured by pressing a ruler against the end face.

[0113] 6. Ignition loss of glass cloth of glass cloth roll (mass%) Test pieces were randomly taken from the glass cloth roll obtained after the surface treatment process and the fiber-spreading process, and measurements and calculations were performed according to the method specified in "7.3.2 Ignition loss" of the Japanese Industrial Standard JIS R 3420:2013 (general test method for glass fibers).

[0114] 7. Glass cloth warp density and weft density of glass cloth roll (threads / 25mm) Using the glass cloth roll obtained by the surface treatment process and the fiber spreading process, measurements and calculations were performed according to the method specified in "7.9 Density (weaving density)" of the Japanese Industrial Standard JIS R 3420:2013 (general test method for glass fibers). Specifically, the measurement targets were positions 50 mm or more away from the ends and ears of the glass cloth, the measurement interval was set to 10 mm or more and 200 mm or less, and the number of all warp and weft threads within the set measurement interval was measured. This was counted as one measurement, and the number of all warp and weft threads within the measurement interval was measured two more times in the same manner by moving to another position that did not include the previously measured warp and weft threads. After every three measurements, the number of warp and weft threads per 25 mm was calculated according to the following formula, and the average value of the three measurements was calculated. Mi = (ni / ai) x 25 Mi: Number of threads per 25mm ni: Number of yarns measured ai: the exact distance at which the measurement was taken (mm)

[0115] 8. Glass cloth mass M (g / m 2 ) Using the glass cloth roll obtained after the surface treatment process and the fiber spreading process, the measurement was performed in accordance with the method specified in "7.2 Mass (mass) of cloth and mat" of "General test method for glass fiber" of the Japanese Industrial Standard JIS R 3420:2013. Specifically, the mass was measured over an area of ​​100 cm from a point 50 mm or more away from the edge of the glass cloth. 2 A square test piece was taken and dried at 105°C for 1 hour, after which the mass of the test piece was measured and the mass of 1m was calculated according to the following formula: 2 The mass per unit was calculated. ρA=(ms / 100)×10 4 ρA:1m 2 Mass per unit (g / m 2 ) ms: mass of test piece (g)

[0116] 9. Glass cloth thickness of glass cloth roll (μm) Using the glass cloth roll obtained after the surface treatment process and the fiber-spreading process, the thickness at both ends and at a location 50 mm or more inward from the edge was measured using an electronic micrometer with a minimum display value of 0.001 mm in accordance with Method B specified in "7.10.1 Cloth thickness" of "General test methods for glass fibers" in the Japanese Industrial Standard JIS R3420:2013.

[0117] 10. Color difference ΔE between the outermost layer and the innermost layer of the glass cloth roll, and L*, a*, and b* of the outermost layer and the innermost layer Using the glass cloth roll obtained by the surface treatment process and the fiber-spreading process, the glass cloth was pulled out from the outermost layer part and the innermost layer part of the glass cloth roll and cut to a length of 50 mm length and 50 mm width to prepare a measurement sample. The sampling position in the weft direction of the glass cloth roll is arbitrary. Next, a polyethylene bag (Shimojima Heiko Poly No. 803) with a thickness of 0.08 mm, width of 80 mm, and depth of 150 mm was prepared, and the prepared measurement samples were stacked in multiple sheets so that each measurement sample did not shift until the thickness reached 4 mm, and placed in the prepared polyethylene bag as it was. Next, 100 g or more of benzyl alcohol with a refractive index of 1.54 was added to the polyethylene bag containing the stacked measurement samples, and the bag was sealed liquid-tight. Then, a color difference meter was used to lightly press the color measurement part against the measurement sample to measure L*, a*, and b*. This was performed for each of the measurement samples of the outermost layer and the innermost layer, and the color difference ΔE between the outermost layer and the innermost layer was calculated using the CIE1976 (L*a*b*) color difference formula.

[0118] 11. Tensile strength of glass cloth roll, tensile strength in warp direction T (N / 25mm) The glass cloth roll obtained by the surface treatment process and the fiber spreading process was used to measure the tensile strength T (N / 25mm) in the warp direction according to the method specified in "7.4.2 In the case of cloth" of the Japanese Industrial Standard JIS R 3420:2013 (General test method for glass fibers). Specifically, a test piece was taken from an arbitrary position of the outermost layer of the glass cloth roll, and a constant-speed extension type tensile tester was used. The measurement conditions were a test piece length of 25 cm, a test piece width (width before the yarns were loosened from both ends) of 30 mm, a grip interval of 15 cm, a test piece width (width after the yarns were loosened from both ends) of 25 mm, and a constant-speed pulling speed of 200 mm / min. The breaking strength was measured five times in the warp direction of the glass cloth, and the arithmetic mean value of the measured values ​​was taken as the tensile strength T (N / 25mm) in the warp direction of the glass cloth. The tensile strength T (N / 25 mm) thus obtained was divided by the mass M of the glass cloth of the glass cloth roll, and the value (T / M) was defined as the tensile strength of the glass cloth in the warp direction.

[0119] 12. Heat resistance of prepreg Using the glass cloth roll obtained after the surface treatment process and the fiber-opening process, glass cloth was pulled out from the outermost and innermost layers of the glass cloth roll and cut to a length of 10 cm length and 10 cm width to prepare a measurement sample. The measurement sample was immersed in an epoxy resin varnish of the following composition, and after being removed from the varnish, the varnish was squeezed out with nip rolls to obtain the following mass ratio, and the sample was subjected to a heat treatment at 150°C for 5 minutes and at 170°C for 1.5 to 2 hours to produce a cured prepreg. The mass (g / m 2 ) to the mass of glass cloth (g / m 2 The proportion of ) was 70 mass %. The obtained prepreg was given a thermal history by the following wet heat treatment and solder bath, and the state of the prepreg thereafter was evaluated according to the following evaluation method.

[0120] (1) Varnish composition Epoxy resin (Mitsubishi Chemical Corporation jER1001B80) 100 parts by weight Hardener (Mitsubishi Chemical Corporation jER Cure DICY7) 3.2 parts by weight (Dicyandiamide) Curing accelerator (Dimethylbenzylamine, manufactured by Tokyo Chemical Industry Co., Ltd.) 0.18 parts by mass Dilution solvent (dimethylformamide manufactured by Kishida Chemical Co., Ltd.) 30 parts by weight

[0121] (2) Heat treatment and solder bath thermal history First, the moist heat treatment was carried out using a pressure cooker. The prepreg was placed inside the pressure cooker and steam pressure was 1.05 kg / cm 2 The test was carried out under conditions of 12 hours at 120°C and an environmental temperature of 121°C. The treatment to give a thermal history in a solder bath was carried out by immersing the heat-moisture treated prepreg in water at 20-25°C for 15 minutes and then immersing it in a solder bath at 260°C for 25 seconds.

[0122] (3) Evaluation method After immersion in the solder bath, the solder adhering to the prepreg was scraped off, and the surface of the prepreg was observed using a flatbed scanner (Epson Corporation) to determine the ratio of the area of ​​the whitened portion (whitened part) to the total area of ​​the prepreg surface. The heat resistance of the composite material was evaluated as follows: if the ratio of the whitened part on the prepreg surface was less than 1%, it was marked as "○", if it was 1% or more but less than 5%, it was marked as "△", and if it was 5% or more, it was marked as "×".

[0123] 13. Resin impregnation of glass cloth First, the following varnish was prepared. [Varnish composition] Epoxy resin (Mitsubishi Chemical Corporation jER1001B80) 100 parts by weight Hardener (Mitsubishi Chemical Corporation jER Cure DICY7) 3.2 parts by weight (Dicyandiamide) Curing accelerator (Dimethylbenzylamine, manufactured by Tokyo Chemical Industry Co., Ltd.) 0.18 parts by mass Dilution solvent (dimethylformamide manufactured by Kishida Chemical Co., Ltd.) 30 parts by weight

[0124] Using the glass cloth roll obtained by the surface treatment process and the fiber-spreading process, the glass cloth was pulled out from the outermost layer and the innermost layer of the glass cloth roll and cut to a length of 10 cm length and 10 cm width to prepare a measurement sample. A glass plate with a polyester film attached was prepared, the measurement sample was placed on the polyester film, and about 1 mL of the above varnish adjusted to a temperature of 20°C was gently poured on top of it, and the impregnation behavior of the glass cloth after 60 seconds was observed and photographed using a stereomicroscope at a magnification of 150 times with transmitted light, and the frequency and maximum length of voids observed in the warp strands constituting the glass cloth were measured to evaluate the impregnation according to the following criteria. In this example, a grade of ○ or higher was considered to be acceptable. Note that voids with a maximum length of 10 μm or more were counted as voids. <Evaluation criteria> No voids observed (number of voids is zero): ◎ Voids are observed, but the maximum length is less than 50 μm: ○ Voids with a maximum length of 50 μm or more are observed, but the maximum length of each is less than 100 μm: △ Voids with a maximum length of 100 μm or more are observed: ×

[0125] [Table 1]

Claims

1. A glass cloth roll in which a glass cloth composed of glass yarns as warp and weft yarns is wound, The mass M of the glass cloth (g / m 2 the tensile strength represented by the ratio (T / M) of the tensile strength T (N / 25 mm) in the warp direction of the glass cloth to the tensile strength T (N / 25 mm) in the warp direction of the glass cloth is 3.8 or more and 6.0 or less; The glass cloth roll has a color difference ΔE between an outermost layer portion and an innermost layer portion of 0.1 or more and 1.5 or less.

2. 2. The glass cloth roll according to claim 1, wherein the color difference ΔE is 0.2 or more and 0.7 or less.

3. A method for producing a glass cloth roll according to claim 1 or 2, A process for preparing a green cloth having a warp ignition loss of 2.5% by mass or more; A water washing process in which the prepared green cloth is washed with water so that the ignition loss of the warp yarn is 2.0% by mass or less; The method for producing a glass cloth roll includes a heat cleaning step of winding the glass cloth that has been subjected to the water washing treatment into a roll having a thickness of 80 mm or less and performing a heat cleaning treatment.

Citation Information

Patent Citations

  • Warp-sizing agent for glass woven fabric and heat-cleaning method for glass woven fabric sized therewith

    JP1995197380A

  • Heat cleaning method for woven glass fiber

    JP2007262629A